Medical Students’ Perception towards Recently Introduced Problem-Based Learning in Surgery Module: A Case of University of Ha’il - Fauwaz Fahad Alrashid, Eyad Mohammed Khalifah, Khalid Farhan Alshammari, Fahaad Saleh Alenazi, Abdulaziz Saad Alqahtani, Mohammed Anizan Alshmmri, Ahmed Alsolami, Sager Holyl Alruwaili, Anas Abdulqader Fathuldeen, Ahmed Onayzan Alshammari, Saadeldin Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In literature, problem-based learning is repeatedly conveyed in relation to medical basic sciences. It has been introduced in the syllabus of the surgery module very recently. Aim: To assess students' perceptions towards PBL in the clinical years course of their medical study, in a surgery module. Methods: A cohort study involves the 6th year students (academic year, 2019-2020) in their surgical course at the end of the newly introduced PBL sessions using a self-administered validated questionnaire. Their responses to close questions had been recorded using a Likert scale. The collected data and their open feedback were analyzed using SPSS version 21. Results: A-80 participants were responded to the questionnaire (male = 46 [57.5%], female = 34 [42.5%]). Their perception of PBL in the surgery module was more positive than negative. Results recognized that student’s perceptions were positive towards the pinpoints of the PBL, precisely in the issues concerned with working in groups, critical thinking and self-learning skills. More than 63% of the participants supposed that the PBL must be preserved as part of the surgery module. However, the number of students who had a negative perception towards PBL process overall was not negligible. Conclusion: PBL is palatable by students, so, it is encouraging to continue adapting this method of learning in the surgery module.